Influência da remoção químico-mecânica do tecido cariado, na adesão à dentina: revisão sistemática e meta-analise - Javorsky, Lucas Spat (2021)
The chemomechanical caries removal agents were developed to facilitating the procedure, making it more conservative and patient-friendly. However, there is no consensus in the literature about their influence on bonding to previously treated dentin. Thus, this study aimed to systematically review the literature for laboratory studies that evaluated the influence of chemomechanical caries removal agents on bonding to dentin. The search for laboratory studies was performed in electronic databases (PubMed, Scopus, ISI Web of Science, and LILACS) using a strategy created by combining specific terms (MeSH) and free terms, with no date or language limitation. The studies were selected according to the inclusion criteria: 1) comparing the chemomechanical caries removal and conventional method, and 2) evaluating the bond strength of adhesive systems. After full-text reading, studies that did not present bond strength values as means and standard deviation, performed the evaluation on sound dentin, or used chemomechanical agents or adhesive systems not commercially available (experimental) were excluded. Two reviewers screened the studies, extracted the data, and assessed the risk of bias. A total of 695 studies were identified, of which 102 were in more than one database (duplicates). Thus, 593 studies were submitted for initial evaluation, of which 39 met the inclusion criteria. Of these, 26 were included in the systematic review and meta-analysis. Chemomechanical caries removal did not impact bond strength values (Z=0.52; p=0.61), regardless of agent (Z=0.64; p=0.52) or adhesive system strategy (Z=0.44; p=0.66). On primary teeth, chemomechanical caries removal agents reduced the bond strength values (Z=2.21; p=0.03). Most studies presented a moderate risk of bias. This systematic review and meta-analysis demonstrated that chemomechanical caries removal does not influence the bond strength of adhesive systems to dentin, except on primary teeth.